Mental health in officials of a chilean university: challenges in the context of COVID-19 - Jorquera Gutiérrez, Ricardo (2020)
The present study aimed to describe the levels of stress, depression and anxiety in workers at a university in northern Chile, in the context of Covid-19. Likewise, it sought to establish the relationship of this symptomatology with exhaustion and work overload, in addition to various sociodemographic and work variables. The results show the presence of stress in 55.7% of the employees, depression in 26% of them and anxiety in 29.2%. The highest rates of stress are observed in women, academics, those under 40 years of age, and in contract workers. The adjustment of a predictive model was empirically verified to show that the perceived work overload allows to explain the work burnout, and, in turn, this variable predicts the stress evidenced by the University workers. It concludes by analyzing the implications of the results in the management of higher education institutions, considering the current pandemic context.